Reviews. Issue 3 (2nd October 2021) - Moreno, Hayley; Parang, Elizabeth; Backowski, Roxanne
Abstract: Elizabeth Parang reviews Open Praxis, Open Access: Digital Scholarship in Action ; Roxanne Backowski reviews Beyond Reality: Augmented, Virtual, and Mixed Reality in the Library.